Вплив карбіду кремнію на мікроструктуру та фазовий склад залізної мішені - Мазанко, В.Ф.; Храновська, К.М.; Стаценко, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
Microscopic structures and the phase composition of an iron target which are formed at alloying by silicon carbide are investigated by electronic and optical microscopies and X-ray analysis. It is established that the combination of complex actions of repeated pulsing mechanical shocks and a pulsing current leads to superdeep penetration of SiC into an iron target. It is shown that the machining under specified conditions leads to the formation of a structure of iron including its silicides and corpuscles of a SiC powder.